VD_FINDINFO HC / 2009 / 423 vom 28. Oktober 2009 - VD Tribunal cantonal (2009)
DILIGENCE, DEVOIR DE COLLABORER, BAIL À LOYER, LOGEMENT, RÉSILIATION ANTICIPÉE, JUSTE MOTIF | 257f al. 3 CO, 257h CO, 274d al. 3 CO, 451 ch. 2 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 470 al. 1 CPC, 13 LTB